Conservative Management for Urethral Foreign Body: A Case Report of an Adolescent Boy With Repeated Events - Bezinque, Adam; Mohamed, Ahmad; White, Jeffrey; Canalichio, Katie; Peppas, Dennis; Rosenberg, Eran (Frontiers in Pediatrics, 2021)
Placing foreign bodies into the urethra is not a common occurrence in the general population. Patients self-insert foreign bodies for a multitude of reasons such as sexual gratification, secondary gain, and psychiatric illness. From our own experience and what has been reported in the literature, there is a wide variability in the type of objects that patients place into the urethra. We report a unique case of a 17-year-old boy with repeated foreign body insertions into the urethra over a 1-year period. This patient suffers from significant psychiatric illness. Due to the number of events in this past year, we have initiated a conservative approach that contrasts the traditional protocol to treat with endoscopic removal. This management has proven to be successful in his case and can be replicated in other scenarios after careful consideration of the clinical presentation.